1998
DOI: 10.1074/jbc.273.4.1998
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Stimulate p21 Gene Expression by Targeting Multiple Transcriptional Elements within a Steroid Responsive Region of the p21 Promoter in Rat Hepatoma Cells

Abstract: Glucocorticoids can induce a G 1 arrest in the cell cycle progression of BDS1 rat hepatoma cells. In these cells, dexamethasone, a synthetic glucocorticoid, stimulated a rapid and selective increase in expression of the p21 cyclin-dependent kinase (CDK) inhibitor mRNA and protein and virtually abolished CDK2 phosphorylation of the retinoblastoma protein. Expression of the p27 CDK inhibitor, and other G 1 -acting cell cycle proteins, remained unaffected. Dexamethasone stimulated p21 promoter activity in a p53-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
2
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 62 publications
(78 reference statements)
5
70
2
5
Order By: Relevance
“…Moreover, TPA-induced skin tumorigenesis was significantly reduced when v-Ha-ras transgene was transferred to cyclin D1-deficient genetic background (Robles et al, 1998). Glucocorticoids or GR overexpression have been reported to induce a G1 cell cycle arrest via an increased expression of p21 that has GRE in its promoter (Ramalingam et al, 1997;Rogatsky et al, 1997Rogatsky et al, , 1999Cha et al, 1998;Park et al, 2001;Terada et al, 2001). The alternative mechanism may involve the transcriptional repression of kB-dependent cyclin D1 (Guttridge et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TPA-induced skin tumorigenesis was significantly reduced when v-Ha-ras transgene was transferred to cyclin D1-deficient genetic background (Robles et al, 1998). Glucocorticoids or GR overexpression have been reported to induce a G1 cell cycle arrest via an increased expression of p21 that has GRE in its promoter (Ramalingam et al, 1997;Rogatsky et al, 1997Rogatsky et al, , 1999Cha et al, 1998;Park et al, 2001;Terada et al, 2001). The alternative mechanism may involve the transcriptional repression of kB-dependent cyclin D1 (Guttridge et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids induce G1 cell cycle arrest in some cell types through the activation of cyclin-dependent kinase (CDK) inhibitors p21/Cip1 and p27/Kip1 (Rogatsky et al, 1997;Cha et al, 1998;Rogatsky et al, 1999;Samuelsson et al, 1999;Park et al, 2001;Terada et al, 2001). Thus, we analysed whether GR affected the expression of p21 and p27 CDK inhibitors, as well as cyclin D1, which is usually overexpressed in skin papillomas (Robles and Conti, 1995).…”
Section: Effect Of Gr Overexpression On Keratinocyte Proliferation Dmentioning
confidence: 99%
“…The transcriptional regulation of specific genes by C/EBP␣ has been found to be a major mechanism in the control of adipose tissue differentiation and energy metabolism. However, the regulation of cell proliferation by C/EBP␣ is more complicated and involves both transcriptional control (3,5,36) and interaction with proteins that regulate cell cycle progression (34). The expression of C/EBP␣ and C/EBP␤ proteins has been shown to be increased in the liver before birth (2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that C/EBP␣ up-regulates p21 mRNA transiently, but protein level elevation occurs primarily via the stabilization of p21 protein (36). It has been recently shown that C/EBP␣ can also up-regulate p21 protein in hepatoma cells (3,5). In the liver, C/EBP␣ regulates p21 protein levels presumably through a protein-protein interaction (34).…”
mentioning
confidence: 99%
“…48 Similarly, GCs stimulated p21 gene expression by targeting multiple transcriptional elements within a steroid responsive region of the p21 WAF1/CIP1 promoter in rat hepatoma cells. 49 Another possibility, not examined in this study, is that DEX may have upregulated some drug-detoxifying factors such as found for metallothionein, [50][51][52] O6-methylguanine-DNA methyltransferase (MGMT), 53-55 P-glycoprotein 56,57 or glutathione, 58 which may have influenced the effectiveness of chemotherapy. 59…”
Section: Effect Of Gcs On Cell Proliferation and Cell Cycle Progressionmentioning
confidence: 99%